Davis, Lydia. Nem vem. Tradução de Branca Vianna. São Paulo: Companhia das Letras, 2017, 126 p. - Marta Freitas Mendes (Cadernos de Tradução, 2019)
Nem vem (Companhia das Letras, 2017), translated by Vianna, is the author's third book translated in Brazil. First published in 2014 in New York by Farrar Publisher Straus & Giroux, it is an anthology of previously released texts, with few changes, in major journals such as Harper’s Magazine, The New York Times and The Paris Review. American Lydia Davis, born in 1947, is a writer, translator, and teacher of creative writing at the University of Albany, NY. Expert in translating French literature into English, she translated Flaubert, Proust and Jouve, and won the 2003 French-American Foundation Translation Prize for her translation of Proust's Swann's Way. Among his fictional works are the novel The End of History (José Olympio, 2016) and four short story anthologies, among which is Types of Disturbance (Companhia das Letras, 2013). In 2013, he won the Man Booker Prize for his work as a whole. Davis is said to be a renewer of English-speaking prose and one of the forerunners of short narrative writing (so-called flash fictions) and unassailable, close to poetry and metaphysical reflection. Branca Vianna is a linguist, translator, interpreter and teacher at PUC-Rio. Bachelor of Arts and Specialist in Simultaneous Interpretation (both from PUC-Rio), Master of Linguistics (University College London) and Master of Interpreter Training (Université de Genève). She translated two works by Lydia Davis for the Companhia das Letras (Types of Disturbance and Neither).